PENGARUH BRAND IMAGE, BRAND AMBASSADOR, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DI E-COMMERCE SHOPEE - Floren Alvoncia; Inda Sukati (LPPM Universitas Putera Batam, 2026)
This research aims to examine the influence of brand image, product quality and product reviews on This research aims to examine the influence of brand image, brand ambassador, and consumer trust on online purchasing decisions on the Shopee e-commerce platform in Batam City. This study employs a quantitative research method. The research sample consisted of 120 respondents who are Shopee users in Batam City and have made at least one purchase. The data collection method used was primary data. Data processing and analysis were conducted using SPSS software. Based on the results of the analysis, this study shows that brand image has a positive and significant effect on purchasing decisions on Shopee in Batam City. In addition, brand ambassador and consumer trust also have a positive and significant influence on purchasing decisions on Shopee in Batam City. Partially, each independent variable significantly affects purchasing decisions. Simultaneously, brand image, brand ambassador, and consumer trust have a positive and significant effect on purchasing decisions on the Shopee e-commerce platform in Batam City.